2012
DOI: 10.5812/numonthly.2232
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Nephrology Referral: Influence on Mortality and Morbidity in Chronic Kidney Disease

Abstract: BackgroundFew studies in India as well as in most developing countries have compared the mortality and morbidity rates between chronic kidney disease patients who were referred early to nephrologists and those who were referred late.ObjectivesTo study the mortality and morbidity patterns and to compare the various clinical parameters between the abovementioned early and late referrals.Patients and MethodsFifty consecutive chronic kidney disease patients were followed up for one year. They were then classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…It is well known that early referral is associated with good clinical outcomes, reduced mortality and hospitalization, and patients had better dialysis preparation . Our present study also suggested that blood pressure, serum phosphorous, and anemia were managed significantly better in early referral compared with late referral.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…It is well known that early referral is associated with good clinical outcomes, reduced mortality and hospitalization, and patients had better dialysis preparation . Our present study also suggested that blood pressure, serum phosphorous, and anemia were managed significantly better in early referral compared with late referral.…”
Section: Discussionsupporting
confidence: 66%
“…It is well known that early referral is associated with good clinical outcomes, reduced mortality and hospitalization, and patients had better dialysis preparation. [1][2][3][4][5] Our present study also suggested that blood pressure, serum phosphorous, and anemia were managed significantly better in early referral compared with late referral. The outcomes of previous studies were focused on mortality, hospitalization, blood pressure, biochemical parameters (serum calcium and phosphorous, hemoglobin, lipid profile, serum albumin), use of erythropoietin, and prevalence of other comorbid diseases (diabetes, cardiovascular disease, heart failure, stroke, chronic obstructive pulmonary disease), but rarely on the psychological factors.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Early referral can help to slow the progression to ESRD and diminished renal function [5,6]. It has also been associated with reduced healthcare costs [7], reduced risk of cardiovascular events [8], reduced risk of early technique failure [9], and lower hospitalization and mortality rates [5,10,11,12,13,14]. Patients who receive an early referral tend to enjoy more quality-adjusted life-years (QALYs) [15], superior placement of dialysis access [12,16], and greater freedom in the selection of dialysis modality [17].…”
Section: Introductionmentioning
confidence: 99%